Phyto, Physicochemical Standardization of Medicinal Plant Enicostemmalittorale, Blume - Vinotha, S.; Ira, T.; Sri Ranjani, S. (Journal of Pharmacy. (IOSR), 2013)
Enicostemma littorale, Blume (Gentianaceae) is a glabrous perennial herb and it is found in open, sandy places among sparse grass close the beach throughout the dry zone in Sri Lanka. It is traditionally used to treat inflammatory and painful conditions like arthritis, back pain; diabetes mellitus and to regulate bowel functions. Phyto, physicochemical standardization of dried, matured whole plants of E. littorale has been carried out in the present study. The study includes organoleptic characters along with estimation of its physicochemical parameters such as loss on drying, pH, ash values, extractability in water and ethanol and preliminary phytochemical screening. The generated information of the present study will provide data which is helpful in the correct identification and authentication of this medicinal plant and may help in preventing its adulteration.
Keywords: Enicostemma littorale; Physicochemical